Dari Quraisy ke MBG: Sakralisasi Dalil QS Quraisy/106 dalam Program Makan Bergizi Gratis - Muh. Sofyan; Abubakar, Achmad; Mahfudz, Muhsin (Dirosah Islamiyah, 2026)
The use of the Quranic verses as a basis for moral legitimacy is a practice rooted in the view that the Quran is the highest guidance (ḥujjah) for Muslims. This article examines the phenomenon of the use of religious arguments, specifically Surah al-Quraish verse 4, by the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN), Nusron Wahid, as the moral-theological basis for the Free Nutritious Meals (MBG) program of President Prabowo Subianto's administration. Through the application of the Critical Discourse Analysis (CDA) approach and the perspective of political interpretation (political hermeneutics). this study examines how religious arguments undergo a process of sacralization and are used as instruments of public policy legitimacy. Data were collected from primary sources in the form of official statements from state officials, the development of MBG implementation from January 2025 to May 2026, and a review of classical and contemporary Quranic interpretation literature. This research finds that this practice poses methodological problems in the field of interpretation, blurs the boundaries between religious discourse and state policy, and has socio-political implications for the program's legitimacy. Furthermore, this study also assesses the potential and challenges of MBG in the context of food security and local agricultural empowerment.